Ultrasound Diagnosis of Congenital Diaphragm Hernia And Successful Outcome After Postnatal Surgery - Yusrawati yusrawati; Putri Mentari Faisal (Universitas Andalas, 2023)
Background: Congenital diaphragmatic hernia (CDH) is a disorder where abdominal contents protrude into the chest. Congenital diaphragmatic hernias are seen in 1 of every 2000-4000 live births. Mortality is predominantly due to the development of pulmonary hypoplasia which is thought to be due to the mass effect on the developing lung.Case Report:Mrs. Y, a 32-year-old controlled for antenatal care at the fetomaternal polyclinic M Djamil hospital. She had no complaints, the patient was referred from another hospital with a suspected fetal diaphragm hernia. The patient is known to be 38-39 weeks term pregnancy, from ultrasound examination found herniation of abdominal contents into the thoracic cavity and. the liquor was excessive and the doppler study was normal. The ultrasound showed normal growth and corresponded to 38 week Then the patient was planned for caesarean section and a hernia repair surgery. The neonate was admitted to the neonatal intensive care unit (NICU). He was shifted to the pediatric surgeon with ventilator support after 48 h and was undergoing surgery. There was a posterolateral left sided defect (BOCKDALEK type) of around 22–24 mm. The intestines were reduced to the abdomen and the closure was done. Immediately after the surgery, the child was admitted back to the NICU and the further postnatal course was uneventful.Discussion and Conclusion: CDH is a malformation of the diaphragm due to failure of closure of the pleuroperitoneal canal at around 10 weeks leading to herniation of abdominal contents into the thoracic cavity leading to compression of lung tissues at pseudo glandular stage. CDH is often ultrasound diagnosed before birth [120, 121]. The intestine and/or the liver may be in the thorax and the lungs are small. US scan allows detailed assessment of the heart. The survival depends on the contralateral lung volume, Ninety percent of cases are due to posterolateral defect which is also called Bochdalek hernia—80% are left sided, 15% are right sided and 5% are bilateral. Herniated viscera leads to pulmonary hypoplasia and pulmonary hypertension. Prognosis depends on the gestational age at diagnosis (earlier the diagnosis, likely larger the defect), associated anomalies, contralateral lung volume, pulmonary vasculature (Doppler), cardiac function, liver herniation and gestational age at delivery